Waste Corn-Cob Cellulose Supported Bio-Heterogeneous Copper Nanoparticles for Aza-Michael Reactions - Sarkar, Shaheen M.; Sultana, Tahnim; Biswas, Tapan Kumar; Lutfor, M. R.; M. M., Yusoff (Royal Society of Chemistry, 2016)
Bio-heterogeneous poly(amidoxime) copper nanoparticles were prepared on the modified surface of waste corn-cob cellulose through a graft copolymerization process. The Cu-nanoparticles (0.05 mol% to 50 mol ppm) selectively promoted the aza-Michael reaction of aliphatic amines to give the corresponding alkylated products at room temperature in methanol. The supported nanoparticles were easy to recover and reused eight times without a significant loss of their activity.